2022
DOI: 10.1111/vco.12829
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survival of dogs with stage 4 oral malignant melanoma treated with anti‐canine PD‐1 therapeutic antibody: A follow‐up case report

Abstract: A monoclonal antibody targeting programmed cell death‐1 (PD‐1) is one of the most promising treatments for human cancers. Clinical studies in humans demonstrated that the anti‐PD‐1 antibody provides a long‐lasting tumour response. Previously, we established an anti‐canine PD‐1 therapeutic antibody (ca‐4F12‐E6), and the pilot clinical study demonstrated that the antibody was effective in dogs with oral malignant melanoma (OMM). However, two OMM cases were still undergoing treatment when the pilot study was publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Recently, a pan-cancer, T-cell-inflamed 18-gene signature indicative of a T-cell-activated tumor microenvironment was reported to be associated with response to PD-1 immune checkpoint blockade, including patients with HNSCC ( 70 , 71 ). A canine anti-PD-1 therapeutic antibody has been developed and a pilot study investigating its safety and efficacy in treating dogs with a variety of spontaneous cancers demonstrated encouraging results, supporting further comparative investigation of this immunotherapy ( 72 , 73 ). Moving forward, investigation of this human T-cell-inflamed gene expression profile in dogs with T cell targeted immunotherapies may also be useful.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, a pan-cancer, T-cell-inflamed 18-gene signature indicative of a T-cell-activated tumor microenvironment was reported to be associated with response to PD-1 immune checkpoint blockade, including patients with HNSCC ( 70 , 71 ). A canine anti-PD-1 therapeutic antibody has been developed and a pilot study investigating its safety and efficacy in treating dogs with a variety of spontaneous cancers demonstrated encouraging results, supporting further comparative investigation of this immunotherapy ( 72 , 73 ). Moving forward, investigation of this human T-cell-inflamed gene expression profile in dogs with T cell targeted immunotherapies may also be useful.…”
Section: Discussionmentioning
confidence: 91%
“…Clinical pilot studies used chimeric or caninized anti-canine PD-1 antibodies and the chimeric anti-canine PD-L1 antibody in dogs with advanced tumors [ 4 11 12 ]; most of those were OMM cases. Our previous studies produced rat-canine chimeric anti-canine PD-1 antibody (ch-4F12-E6) and caninized anti-canine PD-1 therapeutic antibody (ca-4F12-E6) and confirmed that these antibodies can block the binding between canine PD-1 and canine PD-L1 molecules followed by T cell re-activation [ 11 13 ]. We investigated the safety profile and efficacy in 30 dogs with advanced tumors, including OMM (21 cases), mammary gland tumor (MGT, 1 case), SCC (2 cases), renal cell carcinoma (1 case), lymphoma (1 case), sebaceous carcinoma (1 case), lung adenocarcinoma (1 case), and skin melanoma (2 cases), after the safety examination of those antibodies against healthy beagles.…”
Section: Introductionmentioning
confidence: 92%
“…More recently, veterinary medicine has been focusing in the expression and functional analysis of these immune checkpoint molecules and their usefulness as therapeutic targets in animals 22 . In dogs, mAbs against PD-1/PD-L1 have been developed 23 25 , some of which have shown therapeutic efficacy in clinical trials 26 29 .…”
Section: Introductionmentioning
confidence: 99%